Development of Powtoon Animation Web-Based Learning Media for Adaptive Early Childhood Learners Digital Literacy in The Face of A Destructive Era - Sunaryo, Ilham; Fauziati, Endang; Harsono, H; Hikmat, Mauly Halwat; Katoningsih, Sri (Proceedings International Conference on Education Innovation and Social Science, 2024)
The research aims to explain the effectiveness of PAUD teachers in using powtoon animation web-based video media by promoting adaptive children in facing the destructive era . The method in this study uses development that produces products in the form of powtoon animation web-based learning video media. Before using the media, a validation test was carried out by media expert validators and material expert validators. Based on the results that have been obtained, powtoon web-based learning video media is a medium that can and should be used by teachers in teaching at Aisyiyah PAUD throughout Surakarta City. This is indicated by the results of media feasibility which reached an average score of 96.30. Suggestions for PAUD teachers are that this media is expected to be able to facilitate students to learn independently accompanied by parents at home because the ease of technological developments that are right on target will be able to combat destructive content.